2017
DOI: 10.1080/21594937.2017.1348319
|View full text |Cite
|
Sign up to set email alerts
|

Monkey bars, noodles and hay bales: a comparative analysis of social interaction in two school ground contexts

Abstract: The school playground is recognised broadly in the literature as a crucial setting for children to develop social behaviours by engaging in a diverse range of physical and social activities. In this study, we examined children's social interactions in two distinctly different primary school playgroundsa school playground with fixed equipment, and a school playground with moveable play equipment. The aim of this research was to explore how primary school children's social behaviours in schoolyard activities var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…At each observation unit, the observers coded activity types and counted the number of children participating in each activity. We classified playground social behaviours based on the Howes Peer Play Scale (Howes & Matheson, 1992) as used by Mahony and colleagues (Mahony et al, 2017) in their study on LPP and adjusted to our research aims. Because our observations needed to cover the whole playground in very short time frames, we simplified the social play categorization by merging different types of play (simple social interactions, complementary, reciprocal and cooperative play).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At each observation unit, the observers coded activity types and counted the number of children participating in each activity. We classified playground social behaviours based on the Howes Peer Play Scale (Howes & Matheson, 1992) as used by Mahony and colleagues (Mahony et al, 2017) in their study on LPP and adjusted to our research aims. Because our observations needed to cover the whole playground in very short time frames, we simplified the social play categorization by merging different types of play (simple social interactions, complementary, reciprocal and cooperative play).…”
Section: Methodsmentioning
confidence: 99%
“…The social impact of LPP has been examined in different ways. Few studies, mostly qualitative, suggested increase in cooperative play (Bundy et al, 2008; Kuh et al, 2013; Mahony et al, 2017), and one case study found an increase in group connectedness expressed by decreased sex segregation and increased collaborative opportunities for marginalized children (Heravi et al, 2018). Yet, few quantitative studies found no improvement in indicators such as peer acceptance, social skills, peer group size (Gibson et al, 2017), or group connectedness (Gibson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At each observation unit, the observers coded activity types and counted the number of children participating in each type of activity. We classified playground social behaviors based on the Howes Peer Play Scale ( Howes & Matheson, 1992 ) as used by Mahony, Hyndman, Nutton, Smith, and Te Ava (2017) and adjusted to our research aims. The following categories were included: solitary no play (e.g., observing, eating or moving without interactions with other children), solitary play (playing alone or in parallel to others without interacting with them), social no play (e.g., talking), social play (e.g., any playful joint activity, from imaginary play or joint drawing to rough and tumble or soccer), conflict (arguing, fighting or any negative interaction between children equal in power), and bullying (physical or verbal bullying, or other forms of social rejection when children were not equal in power).…”
Section: Methodsmentioning
confidence: 99%